Transparency and Reputation as The Factor Influences to The Intention Waqf: Empirical Studies in Gontor Institution - Azidni Rofiqo; Diyan Novita Sari (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aim to measure and exam the transparency and reputation influence to the intention waqf in Gontor Institution. Professional, trustworthy, and honest management of waqf is the reason Gontor continues to grow rapidly. This paper raises reputation and transparency variables as independent variables, intention to have waqf as the dependent variable. The approach this study is a quantitative approach with structural equation modeling-partial least square (SEM-PLS) measurements. by distributing questionnaires to the community and has 197 respondents. The data were processed using path modeling with SmartPLS 3.32 tools. The results of this study indicate that reputation and transparency have a positive and significant effect on intention to do waqf in the Gontor Institution.